A Metadata-Based Multimodal Model for Resource Sharing of British and American Female Literary Works. (27th April 2022) - Cai, Lanlan
Abstract : Based on the perspective of multimodal teaching theory, this study analyzes the establishment of English and American literature appreciation standard course in universities and discusses the necessity of course offering, multimodal teaching implementation, and multi-evaluation of the course, to provide ideas for English literary teaching reform and talent training in universities. In terms of the training of professional talents, to improve their critical thinking and humanistic quality, a British and American literature course in English major study holds a significant place as a mandatory course for English majors. Basic abilities such as an awareness of Western literature and culture are developed into the ability to appreciate and evaluate literary works. This study, based on the premise of standardizing spatial data and sharing data, argues that the traditional data sharing model has flaws and that a sharing mechanism based on metadata management is required. It also proposes a metadata management strategy that can be used as a model for addressing the problem of heterogeneous storage in data sharing.